UTILIZATION OF SODIUM SULFIT DROPLET FOR OXYGEN ABSORPTION - Anda Lucia (Testing Center for Oil and Gas LEMIGAS, 2018)
Gas absorption by liquid droplets in a spray column is one common method for gas cleaning. The simple design, low pressure drop, and the possibility of its application in liquid systems containing solids are benefi ts of this method. The mass transfer coeffi cient of gas-liquid absorption depends on droplet size, concentration of liquid or gas and the physic-chemical system. Experiments to study the mass transfer using the air-oxygen/sulphite system have been performed. The dispersed droplets were generated by pumping the liquid through a needle with certain fl owrate. A High Speed Camera with shadowgraph method and image processing was used for measurement of droplet size and velocity accurately. The shapes of the droplets were relatively not spherical because of oscillating movement. The droplets are slightly accelerated after detach from the needle. The oxygen concentrations were determined by means of spectrophotometric method. The liquid mass transfer coeffi cients of this experiment are 2 times lower than the model because of the low reaction between oxygen and sulphite . The mass transfer coeffi cient of the experiment is calculated from the experimental data, and compared with the model equations from the literature.